JEWISH ANTAGONISM AS PORTRAYED BY HAMKA IN THE BOOK OF TAFSIR AL-AZHAR - Muhammad, Muhammad; Mahmudi, Zaenul; Hamdan, Ali; S Alahmadi, Fahd Mohana; Rusdi, Mikdar (Islam Futura, 2024)
Abdul Malik Karim Amrullah (Hamka) is widely recognized as a leading Muslim intellectual of 20th-century Indonesia, renowned for his extensive body of work, including both novels and Qur'anic exegesis. His tafsir has been the subject of considerable scholarly interest across Asia. The Qur'an contains numerous verses concerning the Jews, and as an exegete of the entire 30 juz of the Qur'an, Hamka offers a distinct interpretation of these verses. The 20th century was a period marked by significant global political upheaval, notably the establishment of Israel in 1948. The creation of the Israeli state had profound consequences for Muslims worldwide, intensifying anti-Jewish, anti-Zionist, and anti-Israel sentiments, which also permeated discourse in the United States and the United Kingdom. Within this context, several Islamic scholars began to integrate European concepts found in the "Protocols of the Elders of Zion," a document that portrays Jews as malevolent and conspiratorial figures. These ideas gradually infiltrated the field of Qur'anic exegesis, including Indonesian works, most prominently Hamka's Tafsir Al-Azhar, first published in 1965. Before this period, the "Protocols of the Elders of Zion" had not influenced Qur'anic interpretation. This paper seeks to critically analyze the theme of Jewish conspiracy in Hamka's tafsir by tracing the origins of his arguments, identifying the presence of conspiratorial elements in his exegesis, and examining the extent to which Hamka's views converge with those of Sayyid Qutb. The study employs a library-based literature review utilizing a descriptive-analytical and critical approach. The findings reveal that Hamka strongly adheres to the conspiracy theory espoused in the "Protocols of the Elders of Zion," depicting Jews as aiming to establish a new world order, dominate the global economy, and control Hollywood and the media. Moreover, Hamka's interpretations are significantly shaped by Sayyid Qutb's concepts of Jahiliyyah (ignorance) and Hakimiyyah (sovereignty).